Self-Presentation Strategies, Fear of Success and Anticipation of Future Success among University and High School Students - Kosakowska-Berezecka, Natasza; Jurek, Paweł; Besta, Tomasz; Badowska, Sylwia (Frontiers in Psychology, 2017)
The backlash avoidance model (BAM) suggests women insufficiently self-promote because they fear backlash for behaviour which is incongruent with traditional gender roles. Avoiding self-promoting behaviour is also potentially related to associating success with negative consequences. In two studies we tested whether self-promotion and fear of success will be predictors of lower salaries and anticipation of lower chances of success in an exam. In study 1, prior to the exam they were about to take, we asked 234 students about their predictions concerning exam results and their future earnings. They also filled scales measuring their associations with success (fear of success) and tendency for self-promotion. The tested model proved that in comparison to men, women expect lower salaries in the future, anticipate lower test performance and associate success with more negative consequences. Both tendency for self-promotion and fear of success are related to anticipation of success in test performance and expectations concerning future earnings. In study 2 we repeated the procedure on a sample of younger female and male high school pupils (N = 100) to verify whether associating success with negative consequences and differences in self-promotion strategies are observable in a younger demographic. Our results show that girls and boys in high school do not differ with regard to fear of success, self-promotion or agency levels. Girls and boys anticipated to obtain similar results in math exam results, but girls expected to have higher results in language exams. Nevertheless, school pupils also differed regarding their future earnings but only in the short term. Fear of success and agency self-ratings were significant predictors of expectations concerning future earnings, but only among high school boys and with regard to earnings expected just after graduation.